LANDING PAGES IN LOCAL RETAIL: METRICS, EXPERIMENTATION, AND INFRASTRUCTURE DEPENDENCE IN LOW-DEMOGRAPHIC MARKETS - Eugênio, Juliana Ferreira; Reino, Lucas Santiago Arraes (Seven Editora, 2026)
In low-demographic contexts, low traffic volume makes the interpretation of standardized landing page metrics more unstable. This article analyzes a real local retail campaign based on the reanalysis of data from Google Analytics 4, Microsoft Clarity, heatmaps, and interface logs. Methodologically, it is an exploratory case study, with elements of A/B experimentation in a natural environment, guided by Media Ecology, Software Studies, the discussion on platformization, and usability literature. The reanalysis suggests that CTA performance depends on the interface environment, the device, and the funnel stage; that dwell time and scroll depth are useful metrics, but insufficient when interpreted in isolation; and that performance interpretation becomes more aligned with the page’s objective when articulated with signals closer to the payment flow. As a contribution, the article proposes a situated interpretation of performance metrics and derives a lightweight test governance protocol for landing pages in information-scarce contexts.